Modeling of the Function Principle of Semiconductor Gas Sensors for High School Students - Höfner, Sebastian; Hirth, Michael; Kuhn, Jochen; Brück, Benjamin; Schütze, Andreas (International Journal of Online and Biomedical Engineering (iJOE), 2021)
A wide range of pollutants cannot be perceived with human senses, which is why theuse of gas sensors is indispensable for an objective assessment of air quality. Sincemany pollutants are both odorless and colorless, there is a lack of awareness, inparticular among high school students. The project SUSmobil (funded by DBU –Deutsche Bundesstiftung Umwelt) aims to change this. In three modules on the topic ofgas sensors and air quality, the students (1) are familiarized with the functionality of ametal oxide semiconductor (MOS) gas sensor, (2) perform a sensor calibration and (3)carry out environmental measurements with calibrated sensors. Based on theseintroductory experiments, the students are encouraged to develop their ownenvironmental questions. In this contribution, we focus on the experimental andmodeling approach which explains the function principle of a MOS gas sensor in a waysuitable for high school students. This includes a qualitative and quantitativedescription of a simplified sensor model explaining the main processes on the sensorsurface. In addition, an HTML-based self-learning course is presented in which thestudents investigate the sensor behavior in the presence of different substancesdepending on the sensor temperature.